Lokaltherapie solitärer intrapulmonaler maligner Rundherde - Winkel, Jan op den; Eichhorn, Florian; Rieken, Stefan; Dienemann, Hendrik (Der Onkologe, 2017)
Definition: Intrapulmonary nodules generally represent an incidental finding in the roentgenogram or computed tomography (CT) scan of the chest. They are defined as single, well-circumscribed, radiographic opaque lesions that measures up to 3 cm in diameter and are surrounded completely by aerated lung. The probability of malignancy directly correlates with increasing diameter. Lesions that have a diameter of 1 cm or larger require direct evaluation.Therapy: Surgery is the first option for patients with a malignant lesion, given an acceptable perioperative risk; for high-risk patients either radiofrequency ablation (RFA) or stereotactic body radiation therapy (SBRT) should be offered. In these cases the malignant histology has to be established beforehand or verified by radiologic proven growth.Outcome: Complete surgical resection is superior to RFA and SBRT with respect to local tumor control.